NUTRIÇÃO, FISIOLOGIA E PRODUTIVIDADE DE SOJA INOCULADA COM Azospirillum brasilense E REGULADORES VEGETAIS - NONATO, JULIO JOSÉ (2016)
Aiming to evaluate the efficiency of inoculation with Azospirillum brasilense, applied in seeds, furrow and foliar, with or without crescent levels of plant growth regulators in soybean, two studies were conducted in the experimental area of the Universidade Estadual do Centro–Oeste, in Guarapuava, PR, in the season of 2013/2014. The first trial consisted of 4 replications of 11 treatments using commercial inoculant containing A. brasilense, in doses of 2 and 4 ml kg-1 in seeds treatment, 200, 400 and 600 mL ha-1 foliar (V4 stage) and furrow. As for the second trial were 8 treatments with 4 replications, and all the treatments was in seeds, with a steady dose of 3 mL kg-1 of a commercial liquid inoculant with A. brasilense, associated or not to plant growth regulator Stimulate® in doses 0, 2.5, 5 and 7.5 ml kg-1. For both was using completely randomized block design. Soybeans were evaluated: CO2 assimilation rate; stomatal conductance; transpiration; efficient use of water; instantaneous carboxylation efficiency; chlorophyll in SPAD index; levels of macro and micronutrients; productivity; thousand grain weight; activity of superoxide dismutase (SOD), peroxidase (POX) and lipid peroxidation (PL). Data were subjected to analysis of variance and means compared by Tukey test and regression analysis to verify the behavior of the variables depending on the doses of the produc at 1, 5 and 10% probability. From the data obtained, it is observed that the inoculation of bacteria promoted gas exchange increases, increases in accumulation of N, P and S and foliar application had the highest grain yield. It was found that the plant growth regulators, with or without the microorganism presented influences in the activity of SOD, POX and PL, besides increasing the leaf contents of N, P, Ca, Zn, Mn and Cu. It is concluded that the use of these technologies can improve the parameters evaluated for the soybean crop.